2002
DOI: 10.1080/09637480220164370
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of daily breakfast intake, iron deficiency anaemia and awareness of being anaemic among Saudi school students

Abstract: Iron deficiency anaemia is one of most prevalent nutritional disorders worldwide. It is known to affect the health and cognitive ability of children and adolescents. Studies in Saudi Arabia concentrate only on the population of young children and pregnant females or girls. Studies on the whole school student population is lacking. The objectives of this study were to identify the nutritional habits and the prevalence of anaemia among school students in Jeddah, as well as to recognize the students' awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
5
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 21 publications
11
117
5
4
Order By: Relevance
“…SES, either defined by the type of school attended (ie public vs private), by the region of residence (ie rural vs urban) or by the level of parental education (primary school vs University), has been pointed out by many investigators, as an important determinant of the elevated prevalence of iron deficiency and iron deficiency anaemia among the less privileged school-aged children in developing countries (Soekarjo et al, 2001;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2003). Furthermore, the higher incidence of iron deficiency reported for adolescent schoolgirls, compared to boys (Tatala et al, 1998;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2004), shows that female gender exerts an extra effect on the prevalence of this medical condition, probably due to accessional iron losses through menstruation. The findings of the current study indicated that both SES and gender might need closer surveillance, in order to better understand the factors associated with the high prevalence of iron deficiency among urban schoolchildren in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SES, either defined by the type of school attended (ie public vs private), by the region of residence (ie rural vs urban) or by the level of parental education (primary school vs University), has been pointed out by many investigators, as an important determinant of the elevated prevalence of iron deficiency and iron deficiency anaemia among the less privileged school-aged children in developing countries (Soekarjo et al, 2001;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2003). Furthermore, the higher incidence of iron deficiency reported for adolescent schoolgirls, compared to boys (Tatala et al, 1998;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2004), shows that female gender exerts an extra effect on the prevalence of this medical condition, probably due to accessional iron losses through menstruation. The findings of the current study indicated that both SES and gender might need closer surveillance, in order to better understand the factors associated with the high prevalence of iron deficiency among urban schoolchildren in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency is probably the most prevalent and common micronutrient deficiency in the developing world today (Tatala et al, 1998;Asobayire et al, 2001;Abalkhail & Shawky, 2002;Hashizume et al, 2003). The detrimental public health effects of iron deficiency include anaemia, decreased intellectual and work performance as well as functional alterations of the small bowel (Oski, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have reported elsewhere that 9?8 % of pre-school children from the present study's population in Quebec (Canada) ate breakfast on fewer than 7 days per week and that overweight was positively associated with this behaviour (10) . However, other studies show conflicting results, with some revealing a positive association between breakfast skipping and overweight in populations of school children (11,12) and adolescents (13)(14)(15)(16) , while other studies found no significant relationship between breakfast skipping and increased BMI (17,18) . In fact, a recent review suggested that the results remain inconclusive (19) .…”
Section: Breakfast Body Weight Nutrition Childrenmentioning
confidence: 99%
“…In 2003, a global prevalence of 28,24,20,19,17,7 and 2% was estimated for East Asia and the Pacific Islands, Sub-Saharan Africa, South Asia, China, India, the Middle East and North Africa, respectively, and 795 million people were suffering from trichuriasis, particularly younger people . Conversely, iron deficiency remains the most prevalent and common micronutrient deficiency in the developing world (Tatala et al, 1998;Asobayire et al, 2001;Abalkhail and Shawky, 2002;Keskin et al, 2005). In 1991, iron deficiency anaemia (IDA) affected 1.3 billion people (Gillespie et al, 1991); in 2003, the figure increased to about 2 billion (Black, 2003).…”
Section: Introductionmentioning
confidence: 98%